Faktor-Faktor Mempengaruhi IPM di Kota Banjarmasin - Hayati, Norma (PPJP ULM, 2018)
This study aims to determine the effect of government spending on education,health, and social protection simultaneously and partially to the HDI in Banjarmasinfrom 2006 to 2016. The results of the research using the analysis showed that the results of R-square of0.952 could be interpreted that government expenditures in education, health, and socialprotection affect the HDI in the city of Banjarmasin from 2006 to 2016. While partiallyonly in education relevant to IPM city Banjarmasin and health, social protection is notpartly applicable to HDI in Banjarmasin city.